The Danish-Italian Caesar’s Forum Excavations: Preliminary Results from the 2021 Campaign – The Alessandrino Phase - Kindberg Jacobsen, Jan; Murro, Giovanni; Parisi Presicce, Claudio; Raja, Rubina; Grove Saxkjær, Sine; Vitti, Massimo (Archäologischer Anzeiger, 2022)
The Caesar’s Forum Project, initiated in 2017, aims at covering the entire, more than 3,000-year chronological span of the Caesar’s Forum area. The first phase of the archaeological investigations has unearthed structures in the archaeologically under-researched Alessandrino Quarter, which was demolished to make way for Mussolini’s Via dell’Impero. This article presents the first detailed overview of the second excavation phase undertaken within the new Danish-Italian project and the new archaeological insights brought to light.